DOI: 10.26686/wgtn.16967875
|View full text |Cite
|
Sign up to set email alerts
|

The Social Environment of Public Transport

Abstract: <p>Crowding is identified both internationally and in New Zealand as a key issue in public transport. Unfortunately, the concerns of public transport providers are focussed on economic imperative rather than a concern for the actual experiences of patrons. The social needs of public transport passengers are neglected, both in practice and in research. This research examines the delicate balance between the need for privacy and the need for social interaction in the setting of public transport. These need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 102 publications
(298 reference statements)
0
1
0
Order By: Relevance
“…decisions around how to place virtual displays and content in transit contexts [62]. Prior research has shown that "the seating layout of public transport forces people into an intimate distance with strangers, causing social discomfortž [99] which could be expected to impact attitudes towards AR-oriented interaction techniques.…”
Section: Social Acceptabilitymentioning
confidence: 99%
“…decisions around how to place virtual displays and content in transit contexts [62]. Prior research has shown that "the seating layout of public transport forces people into an intimate distance with strangers, causing social discomfortž [99] which could be expected to impact attitudes towards AR-oriented interaction techniques.…”
Section: Social Acceptabilitymentioning
confidence: 99%